A study on fire fighting system at historical shophouses / Noor Azlinda Azman - Azman, Noor Azlinda (2005)
Fire fighting is important for all buildings which one of them is historical shophouses. Historical shophouses have a high value which shows legend of certain place and image of the place itself. Although the premise's age is more than 70 years but it is important to care it especially prevent it from fire. Fire can make people loss valuable properties including their life. Recently, all parties have generally tried to increase the fire awareness but fire still happen whether by human fault or for other reasons. So it is important if all shophouses are install with firefighting equipment to prevent their building if fire occur. Tenants or owner of the building itself should be exposed to fire prevention skills and fire safety to make sure that they will know how to take action if their premise have fire.